Effect of land use, time of day and vehicle type on seat belt use in Lagos, Nigeria (2012)
The seat belt has been proven to be effective in the reduction of traffic injuries and deaths. Despite the efficacy and strict enforcement of legislation, it has been frequently underutilized in many countries including Nigeria.The aim of this study was to investigate the seat belt use rate, and determine the effect of land use types, vehicle types and time of day on observed rates in a local government area of Lagos state, Nigeria. A two-day cross-section observational survey was conducted in three observation points, The use rates by land use type, time of day and vehicle type were observed. A total of 40,753 vehicles were evaluated. In general, 43.1 percent of drivers observed used the seat belt. The highest seat belt compliance rate was observed in the residential sector (55.8%), among private cars (65.1%), and between 1.00pm and 4.00pm (44.8%). The chi-square analysis confirmed significant differences in seat belt use across three land use types (X2=609.72, p = 0.001), vehicle types (X2= 11780.31; p = 0.001) and time of day (X2- 59.86; p= 0.001). More seat belt education and stricter enforcement of the seat belt regulation were suggested to raise the level of seat belt use in concerned areas, vehicle types and at the affected time intervals.